Congenital Unilateral Agenesis of the Parotid Gland: A Case Report and Review of the Literature. (8th November 2016) - Teymoortash, Afshin; Hoch, Stephan
Abstract : Congenital unilateral agenesis of the parotid gland is a rare condition with only few cases reported in the literature. A review of 21 cases in the available literature is presented in this article. We report on a further case of a 34-year-old woman with agenesis of the left parotid gland and lipoma of the right cheek. Clinicopathological characteristics of described cases in the literature were discussed.